Age-dependent effects on infectivity and susceptibility to SARS-CoV-2 infection: results from nationwide contact tracing data in Greece. Issue 3 (4th March 2022) - Bistaraki, Angeliki; Roussos, Sotirios; Tsiodras, Sotirios; Sypsa, Vana
Abstract: Background: Understanding the factors that affect the transmissibility of SARS-CoV-2 remains important to keep transmission low and maximize the health benefits of vaccination. We assessed the factors associated with the transmissibility of SARS-CoV-2 based on contact tracing data. Methods: From 1 October to 9 December 2020, 29, 385 laboratory-confirmed SARS-CoV-2 cases (index cases, i.e. the first identified laboratory-confirmed cases or with the earliest symptom onset in a setting) and 64, 608 traced contacts were identified in Greece. We assessed the prevalence of symptoms in cases, calculated secondary attack rates and assessed factors associated with infectivity and susceptibility to infection. Results: There were 11, 232 contacts secondarily infected (secondary attack rate: 17.4%, 95% CI:17.0–17.8). Contacts aged 0–11 and 12–17 years were less susceptible to infection than adults 65 years or older (odds ratio (OR) [95% CI]: 0.28 [0.26–0.32] and 0.44 [0.40–0.49], respectively). Index cases aged 65 years or older were more likely to infect their contacts than other adults or children/adolescents. The odds of infection [95% CI] were higher in contacts exposed within the household (1.71 [1.59–1.85] vs. other) and in cases with cough (1.17 [1.11–1.25] vs. no cough). There was an interaction between the age of the index and the age of the contact with contacts 65 years or older having a higher probability of infection when exposed to cases of similar age than to children. Conclusions: Our findings highlight the role of age and age mixing in infectivity and susceptibility to SARS-CoV-2 infection. Precautions are necessary for individuals 65 or older as they have higher infectivity and susceptibility in contact with their peers.